Analisis Muatan IPS Keberagaman Budaya dalam Film"Adit dan Sopo Jarwo” Episode “Ondel-Ondel Bikin Denis Jengkel” - Tsani Shofiah Nurazizah; Zakiah Ulfiah; Yona Wahyuningsih (Journal on Education, 2023)
One of the social studies contents for grade IV SD is about Social and Cultural Diversity in Indonesia. In the midst of rapid technological developments, some traditional and hereditary activities have been replaced by activities contained in technological products such as gadgets. Therefore, cultural learning is very important to be introduced to students. One way that can attract students to know and get to know culture is by watching animated films because students are more interested in moving images that involve audio-visual activities. One of the educational animated films is the animated series 'Adit dan Sopo Jarwo' with one episode of “Ondel-Ondel Make Denis Angry” which is suitable for social and cultural content. The method used in this research is literature study and film analysis. The results of the research based on film analysis found that the animated film series "Adit & Sopo Jarwo: Ondel-Ondel Bikin Denis Jengkel" contained IPS content about social and cultural diversity in Indonesia, such as the Betawi language and Batak accent, the typical Betawi art, namely Ondel. -Ondel, and traditional games, namely Sondah and Kelereng.